PFA composite material laminate and preparation method thereof

CNT-PFA micropowder containing carbon nanotubes was synthesized through in-situ emulsion polymerization technology, and distributed on the surface of the spreading carbon fibers through coating and casting processes to form a laminated plate of PFA composite materials, solving the problem of poor temperature resistance in high temperature and strong oxidative environments, improving the degree of bonding and mechanical properties, and suitable for semiconductor processes.

CN119261333BActive Publication Date: 2025-03-11SHANGHAI MORISEAL NEW MATERIAL TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411783160.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The existing fiber-reinforced resin composites show poor temperature resistance in high temperature and strong oxidizing solvent environments, and the degree of bonding between carbon fiber and matrix resin is difficult to reach the appropriate level, which affects its mechanical properties.

Method used

Tetrafluoroethylene-perfluoroalkylvinyl ether polymer (CNT-PFA) emulsion containing carbon nanotubes was synthesized by in-situ emulsion polymerization technology, and CNT-PFA micropowder was obtained, and it was evenly distributed on the surface of the spreading carbon fibers through coating and casting processes to form a PFA composite laminate.

Benefits of technology

The dispersion of carbon nanotubes and carbon fibers in the PFA resin matrix is ​​improved, the degree of bonding between carbon nanotubes and carbon fibers and matrix resin is improved, and the high-temperature resistance and mechanical properties of composite materials are enhanced, and it is suitable for high-temperature harsh environments in semiconductor processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119261333B_ABST
    Figure CN119261333B_ABST
Patent Text Reader

Abstract

The present invention provides a PFA composite laminate and a preparation method thereof, which belongs to the technical field of perfluororesins. The method includes polymerizing carbon nanotubes with tetrafluoroethylene monomers and perfluoroalkyl vinyl ether monomers to obtain a PFA emulsion containing CNTs, drying and devolatilizing to obtain a PFA powder containing CNTs; applying the PFA powder to the surface of a spun-yarn carbon fiber and drying it to form a prepreg; melt-extruding and granulating the PFA powder to obtain a PFA cast film; superimposing the PFA cast film with the spun-yarn carbon fiber prepreg in different film-forming directions, vacuum exhausting, and compression molding to obtain a laminate; superimposing the laminates in sequence, vacuum exhausting, and compression molding to obtain a PFA composite laminate. Through the processing scheme of the present application, the tensile strength of the PFA composite laminate in the x-y direction and the z-axis direction is improved, and it can be applied to semiconductor processes involving high temperature and strong oxidizing solvent environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of perfluororesins, and in particular to a PFA composite material laminate and a preparation method thereof. Background Art

[0002] The molding method of thermoplastic resin composites is mainly borrowed from thermosetting resin composites and metal molding technology. However, the actual application of thermoplastic resins and their composites is far from the original optimistic estimate, mainly because the bonding degree between carbon fiber and matrix material in thermoplastic resin composites is difficult to reach the expected level, and the potential mechanical properties of composite materials cannot be fully utilized. At the same time, it is also subject to factors such as harsh molding process conditions and high manufacturing costs. Therefore, the key to thermoplastic resin carbon fiber composites is to start with improving the bonding strength between carbon fiber and thermoplastic resin, improve interface bonding, and obtain higher performance thermoplastic resin carbon fiber composites.

[0003] There are two main aspects to the bonding degree between carbon fiber and matrix material in thermoplastic resin carbon fiber composites: one is the technology to improve the adhesion between carbon fiber and resin interface. The other is to improve the dispersion of carbon fiber in thermoplastic resin matrix. The technology that can improve the bonding degree between carbon fiber and matrix resin in thermoplastic resin composites is also the key technology of thermoplastic resin carbon fiber composites.

[0004] Fiber reinforced polymer composites (FRP) are new composite materials made by combining fiber and resin in a certain way. Fiber has high strength, high modulus, and small elongation at break when damaged, while resin has low strength, small modulus, and good plasticity, which can reduce the brittle effect of carbon fiber. At the same time, it can play a role in bonding fibers, transferring loads, ensuring the orientation of reinforced fibers, and protecting fibers from wear in composite materials. Therefore, by combining the two, taking advantage of their strengths and making up for their weaknesses, a new material with relatively superior performance can be prepared.

[0005] In the semiconductor process, a high temperature and a strong oxidizing solvent environment are often required. Existing fiber-reinforced resin composites, such as carbon fiber-reinforced PFA composites, have a low modulus in the z direction. At the same time, in order to increase the carbon fiber content, PFA with a higher melt flow index MFR needs to be used for impregnation to improve the impregnation effect, resulting in poor temperature resistance of the composite material.

[0006] Therefore, with the development of the semiconductor industry, it is urgent to develop a PFA composite material that can withstand high temperatures and adapt to strong oxidizing solvent environments. Summary of the invention

[0007] Therefore, in order to overcome the above-mentioned shortcomings of the prior art, the present invention provides a PFA composite laminate and a preparation method thereof.

[0008] In order to achieve the above object, the present invention provides a method for preparing a PFA composite laminate, comprising:

[0009] S1, polymerizing carbon nanotubes with tetrafluoroethylene monomer and perfluoroalkyl vinyl ether monomer to obtain a tetrafluoroethylene-perfluoroalkyl vinyl ether polymer emulsion containing CNTs, demulsifying and condensing the emulsion, washing, vacuum drying and devolatilizing to obtain CNT-PFA micropowder;

[0010] S2, coating the CNT-PFA powder onto the surface of the surface-impregnated and modified spun carbon fiber, and drying to obtain a spun carbon fiber prepreg; and melt-extruding another portion of the CNT-PFA powder to form a granulated cast film to obtain a CNT-PFA cast film;

[0011] S3, alternately stacking the CNT-PFA cast film with the spun carbon fiber prepreg in different film-forming directions to form a laminated plate A, and performing vacuum exhaust molding on the laminated plate A at a certain temperature to obtain a laminated plate with a number of layers a;

[0012] S4, stacking the laminated plates with a number of layers a in sequence to form a laminated plate B, and performing vacuum exhaust compression molding on the laminated plate B at a certain temperature to obtain a PFA composite laminated plate with a number of layers b.

[0013] In one of the embodiments, in step S1, 1-5 parts by mass of hydrophobic carbon nanotubes are ground and ultrasonically dispersed in a perfluoropolyether with active end groups to obtain a CNT perfluoropolyether suspension, and then emulsion polymerized with 90-99 parts of tetrafluoroethylene monomer TFE and 1-10 parts of perfluoroalkyl vinyl ether monomer to obtain a tetrafluoroethylene-perfluoroalkyl vinyl ether polymer emulsion containing carbon nanotubes, and a flocculant is added for coagulation, washing, and drying and devolatilization to obtain the CNT-PFA micropowder, wherein the active end group in the perfluoropolyether with active end groups is carboxyl -COOH or hydroxymethyl -CH2OH.

[0014] In one embodiment, in step S1, the perfluoroalkyl vinyl ether is at least one of perfluoromethyl vinyl ether, perfluoroethyl vinyl ether and perfluoropropyl vinyl ether.

[0015] In one embodiment, in step S1, the drying and devolatilization temperature is 200-280°C, the pressure is 0.01-0.03 MPa (absolute pressure), and the time is 10-24 hr.

[0016] In one embodiment, the spreading carbon fiber is a method of mechanically expanding the carbon fiber bundle using multiple rollers.

[0017] In one embodiment, the yarn spreading uses multiple rollers that can move up and down, and the fibers are shaken out and spread out by vibrating up and down to achieve the desired width; the yarn spreading ratio is 2-5 times.

[0018] In one embodiment, the surface of the spread carbon fiber is modified by an impregnating agent, wherein the impregnating agent is a solution of perfluoropolyether with active end groups, and the solvent in the solution of perfluoropolyether with active end groups is trichlorotrifluoroethane (F113) or hexafluoroxylene (HFX).

[0019] In one embodiment, the cast film is prepared by longitudinal casting, transverse casting or double casting, and the thickness of the PFA cast film is 0.01-0.35 mm.

[0020] In one embodiment, the particle size of the CNT-PFA powder is 1-1000 μm.

[0021] In one embodiment, in S2, the coating process can be repeated, including single-sided coating, double-sided coating, or coating after drying.

[0022] In one of the embodiments, in S3, the superimposed plate A is obtained by sequentially stacking the CNT-PFA cast film and the spread carbon fiber prepreg; or the superimposed plate A is obtained by stacking two layers of the CNT-PFA cast film and a single layer of the spread carbon fiber prepreg layer by layer, and in the superimposed plate A, the CNT-PFA cast film is stacked in the film forming direction of 0°, 45° or 90°.

[0023] In one embodiment, in S3, the stacked plate A is heated to 260-280°C, evacuated, and then heated to 300-320°C for compression molding at a compression molding pressure of 0.1-5 MPa; and then cooled to room temperature while maintaining the pressure to obtain the laminate with a number of layers a.

[0024] In one embodiment, in S4, the laminated plate B is heated to 260-280°C, evacuated, and then heated to 300-320°C for compression molding at a compression molding pressure of 0.1-5 MPa; and then cooled to room temperature while maintaining the pressure to obtain the PFA composite laminate with a number of layers b.

[0025] In one embodiment, the value range of a is 10-50 layers, and the value range of b is 5-20 layers.

[0026] In one of the embodiments, the mass of carbon nanotubes and carbon fibers in the PFA composite laminate accounts for 5-15% of the total composite mass.

[0027] Compared with the prior art, the advantages of the present invention are:

[0028] By using in-situ emulsion polymerization technology, the CNT-containing PFA emulsion is demulsified, condensed and washed, and then vacuum dried and devolatilized to ensure that the obtained CNT-PFA powder has a small particle size, and the CNT-PFA powder is evenly distributed on the surface of the spread carbon fiber by a coating process. In order to improve the adhesion effect of the CNT-containing PFA particles to the spread carbon fiber, the surface of the spread carbon fiber is pre-impregnated with a perfluoropolyether with an active end group. The PFA emulsion containing carbon nanotubes CNT is synthesized by emulsion polymerization to increase the surface energy of the PFA emulsion and reduce its inertness, and then the CNT-PFA powder is coated on the surface of the surface-modified spread carbon fiber and dried to form a spread carbon fiber prepreg; another part of the CNT-PFA powder is melt-extruded, granulated and cast to obtain a PFA cast film; the dispersion of carbon nanotubes and carbon fibers in the PFA resin matrix is ​​improved, and the bonding degree between carbon nanotubes and carbon fibers and the matrix resin in the PFA resin-based composite material is improved.

[0029] By in-situ synthesizing CNT-PFA, the content of CNT and carbon fiber in the composite material is increased while maintaining high temperature resistance. The tensile modulus in the z direction is increased while maintaining the tensile modulus in the xy direction. The prepared PFA composite laminate can be used in high temperature and harsh environments in semiconductor manufacturing processes. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 This is a method for preparing a PFA composite laminate in an embodiment of the present invention. DETAILED DESCRIPTION

[0032] The embodiments of the present application are described in detail below with reference to the accompanying drawings.

[0033] The following describes the implementation methods of the present application through specific examples, and those skilled in the art can easily understand other advantages and effects of the present application from the contents disclosed in this specification. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The present application can also be implemented or applied through other different specific implementation methods, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present application. It should be noted that, in the absence of conflict, the following embodiments and the features in the embodiments can be combined with each other. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present application.

[0034] It should be noted that various aspects of the embodiments within the scope of protection of the present invention are described below. It should be apparent that the aspects described herein can be embodied in a wide variety of forms, and any specific structure and / or function described herein is merely illustrative. Based on the present application, it should be understood by those skilled in the art that an aspect described herein can be implemented independently of any other aspect, and two or more of these aspects can be combined in various ways. For example, any number and aspect described herein can be used to implement the device and / or practice the method. In addition, other structures and / or functionalities other than one or more of the aspects described herein can be used to implement this device and / or practice this method.

[0035] It should also be noted that the illustrations provided in the following embodiments are only schematic illustrations of the basic concept of the present application. The drawings only show components related to the present application rather than being drawn according to the number, shape and size of components in actual implementation. In actual implementation, the type, quantity and proportion of each component may be changed arbitrarily, and the component layout may also be more complicated.

[0036] Additionally, in the following description, specific details are provided to facilitate a thorough understanding of the examples. However, it will be understood by those skilled in the art that the aspects described may be practiced without these specific details.

[0037] Tetrafluoroethylene-perfluoroalkyl vinyl ether monomer copolymer, referred to as PFA, not only retains almost all the excellent properties of polytetrafluoroethylene, but also can be melt processed.

[0038] Carbon fiber is the reinforcement of composite materials. The wettability between carbon fiber and resin directly determines the mechanical properties of the composite material. Moreover, the wettability depends on the surface energy of the fiber and the surface tension of the resin, both of which are important physical quantities that reveal the action mechanism of resin fiber.

[0039] The surface energy of carbon fiber is between 37-48 mN / m, while the surface energy of PFA is about 20 mN / m. The surface energy of the two is quite different. When the two are used to make composite materials, it is necessary to improve the bonding degree between carbon fiber and matrix perfluororesin. PFA has extremely low surface energy and poor wettability. It is a highly inert material and has poor compatibility with most fillers. In addition, the surface of carbon fiber is too smooth, has high surface inertness, and has low surface energy, so it has poor bonding with the resin matrix. In order to improve the interfacial bonding between carbon fiber and PFA matrix, carbon fiber must be properly surface treated. However, conventional treatment methods such as room temperature coupling agents and epoxy resins fail at high temperatures.

[0040] like Figure 1 As shown, the present application embodiment provides a method for preparing a PFA composite laminate, comprising:

[0041] S1, polymerizing carbon nanotubes with tetrafluoroethylene monomer and perfluoroalkyl vinyl ether monomer to obtain CNT-containing tetrafluoroethylene-perfluoroalkyl vinyl ether polymer (CNT-PFA) emulsion, demulsifying and condensing the emulsion, washing, vacuum drying and devolatilization to obtain CNT-PFA micropowder.

[0042] The diameter of carbon nanotubes (CNT) is 2-4 nm, the length is 5 μm, and the aspect ratio is very large. CNTs are ground in perfluoropolyether with active end groups and ultrasonically dispersed to obtain CNT perfluoropolyether suspension, and the CNT perfluoropolyether suspension is emulsion-polymerized with tetrafluoroethylene and perfluoroalkyl vinyl ether monomers to obtain CNT-containing tetrafluoroethylene-perfluoroalkoxy polymer (CNT-PFA) emulsion, and carbon nanotubes are used to modify the PFA emulsion through an in-situ synthesis reaction. The emulsion is demulsified and condensed, and the pH of the emulsion is adjusted to about 3 with hydrochloric acid, and a 20% magnesium chloride solution is added dropwise while stirring for flocculation. Initiators, surfactants, buffer substances, chain transfer agents, etc. can be added as needed in the in-situ synthesis reaction. Perfluoropolyethers with active end groups mainly include Solvay's Fomblin Z series and DuPont's Krytox series. In one embodiment, Fomblin Z type perfluoropolyether (PFPE) produced by Solvay is used, including Fomblin Z DOL (end group -CH2OH) or Fomblin Z Diac (end group -COOH). The molecular weight of Fomblin Z DOL or Fomblin Z Diac is about 2000-4000.

[0043] In one embodiment, 1-5 parts by mass of hydrophobic carbon nanotubes CNT are polymerized with 90-99 parts of tetrafluoroethylene TFE and 1-10 parts of perfluoroalkyl vinyl ether monomers to obtain a tetrafluoroethylene-perfluoroalkoxy polymer PFA emulsion modified with CNT. After the emulsion is condensed, it is slurried in water for many times, the polymer is washed, and then filtered. The washing process removes most of the water-soluble components. The wet PFA powder is dried in a vacuum at about 40-80 ° C, with a moisture content of less than 0.1%, and then heated to 200-280 ° C for devolatilization, and the volatile matter is further removed in the subsequent vacuum drying process.

[0044] S2, coating CNT-PFA powder onto the surface of the surface-impregnated modified spun carbon fiber, and drying to obtain the spun carbon fiber prepreg; melt-extrude the other part of the CNT-PFA powder to form a granulated cast film.

[0045] Carbon fiber refers to high-strength and high-modulus fiber with a carbon content of more than 90%. Spreading carbon fiber can be obtained by processing carbon fiber bundles using ultrasonic fiber expansion method, air jet fiber expansion method, and sonic fiber expansion method.

[0046] When ultrasonic waves propagate in liquid, they can form cavities in the solution. The cavities are in a vacuum state, and the gas in the solution enters the cavities to form bubbles. When the bubbles are formed, they burst under the action of pressure and generate powerful shock waves, generating 0.5~20T / cm around them. 2 The ultrasonic fiber expansion method uses the ultrasonic cavitation effect to impact the carbon fiber bundle to achieve the purpose of expanding the fiber.

[0047] The air jet fiber expansion method is to spray compressed air onto the fiber surface, and use the jet air perpendicular to the fiber direction to bend the carbon fiber bundle while moving along the width direction to push the carbon fiber bundle to expand.

[0048] The sonic fiber expansion method uses low-frequency sound waves to vibrate carbon fiber bundles in a gas medium to expand the carbon fiber bundles.

[0049] The spread carbon fiber described in the present application is a carbon fiber bundle that is expanded by a mechanical multi-group roller expansion method. In one embodiment, multiple rollers that can move up and down are used to shake the fibers and spread the fiber bundle by vibrating up and down to achieve the desired width; the spread carbon fiber has an expansion ratio of 2-5 times that of the carbon fiber bundle, that is, the width of the spread carbon fiber is 2-5 times the width of the carbon fiber bundle.

[0050] In one embodiment, in order to facilitate the coating of CNT-PFA powder, the surface of the spread carbon fiber is wetted before coating.

[0051] CNT-PFA powder is melted and extruded into granules to obtain CNT-PFA pellets, which are then cast into films. Specifically, CNT-PFA resin is added to the extruder hopper, plasticized by screw extrusion, and then extruded through a casting die to obtain a molten film, which passes through a first temperature-controlled casting roller, a second temperature-controlled cooling roller, and a third temperature-controlled cooling roller after leaving the casting die, and is fully cooled and shaped to obtain a CNT-PFA casting film. The temperature of the latter roller is usually lower than that of the previous roller. These temperature-controlled rollers fully control the cooling rate after the molten film leaves the casting die. In some embodiments, additional rollers can also be used for further control. The thickness of the CNT-PFA casting film is controlled within 0.01-0.35 mm.

[0052] For example, CNT-PFA resin is added to the hopper of the extruder, and passes through the three heating zones, connection zone, screen changing zone and distribution zone of the extruder in sequence, and is fully plasticized by screw extrusion to obtain molten CNT-PFA; then it is extruded through the casting die to obtain a molten film, and after leaving the casting die, the molten film passes through the first temperature-controlled casting roller, the second temperature-controlled cooling roller and the third temperature-controlled cooling roller, and is fully cooled and shaped to obtain a CNT-PFA cast film. The temperature of the first heating zone of the extruder is controlled to be 250-310℃, the temperature of the second heating zone is 310-390℃, the temperature of the third heating zone is 320-390℃, the temperature of the connection zone is 320-390℃, and the temperature of the screen changing zone is 320~390℃. The temperature of the casting film head is maintained at 340℃.

[0053] S3. Alternately stacking the CNT-PFA cast film with the spread carbon fiber prepreg in different film-forming directions to form a laminate A, and performing vacuum exhaust molding on the laminate A at a certain temperature to obtain a laminate with a number of layers a.

[0054] The CNT-PFA cast film is stacked with the spread carbon fiber prepreg in the film forming direction of 0°, 45° or 90° to eliminate stress, and vacuum evacuated at a certain temperature and compression molded to obtain a first laminate with a number of layers a.

[0055] The stacking plate A can be stacked in sequence by at least one layer of CNT-PFA cast film and one layer of spread carbon fiber prepreg. In the stacking plate A, all CNT-PFA cast films are stacked in the direction of 0°, 45° or 90° of the film forming direction.

[0056] For example, the CNT-PFA cast films can be stacked in sequence at 0°, 45° or 90° in the film forming direction; the CNT-PFA cast films can be stacked in sequence at 0°, 90° or 45° in the film forming direction; or the CNT-PFA cast films can be stacked in random order at 0°, 90° or 45° in the film forming direction, as long as the internal stresses of the final laminate offset each other.

[0057] S4. Stacking the laminates with a number of layers a in sequence to form a laminated plate B, and performing vacuum exhaust molding on the laminated plate B at a certain temperature to obtain a PFA composite laminate with a number of layers b.

[0058] The laminates are stacked one after another, vacuum-exhausted and compression-molded to obtain a PFA composite laminate having b layers. There is no specific correlation between the values ​​of a and b.

[0059] A PFA composite material laminate can be prepared by the above method, and the PFA composite material laminate can be used in high-temperature and harsh environments of semiconductor manufacturing processes.

[0060] PFA composite laminates can be used in hydrophilic bonding technology in semiconductor manufacturing, such as preparing containers for hydrophilic bonding reactions. Hydrophilic bonding technology mainly uses RCA solution (a mixed aqueous solution of ammonia and hydrogen peroxide) or piranha solution (a mixed solution of concentrated sulfuric acid and hydrogen peroxide) to clean the clean and polished wafer surface to form a hydrophilic surface with a high density of hydroxyl groups (-OH). Water molecules in the environment are easily adsorbed on the hydrophilic surface, thereby bonding two wafers with hydrophilic surfaces together.

[0061] In one embodiment, in step S1, the perfluoroalkyl vinyl ether is at least one of perfluoromethyl vinyl ether, perfluoroethyl vinyl ether and perfluoropropyl vinyl ether.

[0062] In one embodiment, in step S1, the drying and devolatilization temperature is 200-280°C, the pressure is 0.01-0.03 MPa (absolute pressure), and the time is 10-24 hr.

[0063] In one embodiment, the spreading carbon fiber is a method of mechanically expanding the carbon fiber bundle using multiple rollers.

[0064] In one embodiment, a plurality of rollers that can move up and down are used to shake out and spread the fiber bundles by vibrating up and down to achieve a desired width; the yarn spreading ratio is 2-5 times.

[0065] In one embodiment, the surface of the spread carbon fiber is modified by an impregnating agent, wherein the impregnating agent is a solution of perfluoropolyether with active end groups, and the solvent in the solution of perfluoropolyether with active end groups is trichlorotrifluoroethane (F113) or hexafluoroxylene (HFX).

[0066] In one embodiment, the cast film is prepared by longitudinal casting, transverse casting or double casting, and the thickness of the PFA cast film is 0.01-0.35 mm.

[0067] Longitudinal casting mainly involves stretching in the longitudinal direction. This process is usually used to produce film products with specific directional performance requirements. In the longitudinal casting process, the material is mainly stretched in the longitudinal direction to obtain the desired physical properties.

[0068] Transverse casting is stretched in the transverse direction. This process is suitable for film products that require transverse strength or specific properties. During the transverse casting process, the material is mainly stretched in the transverse direction to meet specific application requirements.

[0069] Double-stretch casting combines the two processes of longitudinal stretching and transverse stretching, that is, stretching in two directions at the same time. This process is suitable for film products that require comprehensive performance. By stretching in two directions at the same time, better comprehensive physical properties can be obtained.

[0070] In one embodiment, the particle size of the CNT-PFA powder is 1-1000 μm.

[0071] In one embodiment, in S2, the coating process can be repeated, including single-sided coating, double-sided coating, or coating after drying.

[0072] In one embodiment, in S3, the superimposed plate A is obtained by sequentially superimposing the CNT-PFA cast film and the spun carbon fiber prepreg; or the superimposed plate A is obtained by sequentially superimposing two layers of the CNT-PFA cast film and a single layer of the spun carbon fiber prepreg. In the superimposed plate A, the CNT-PFA cast film is superimposed in the film forming direction of 0°, 45° or 90°.

[0073] In one embodiment, in S3, the stacked plate A is heated to 260-280°C, vacuum exhausted, and then heated to 300-320°C for compression molding, with a compression molding pressure of 0.1-5 MPa; and then cooled to room temperature while maintaining the pressure to obtain a laminate with the number of layers a.

[0074] In one of the embodiments, in S4, the stacked plate B is heated to 260-280°C, evacuated, and then heated to 300-320°C for compression molding at a compression molding pressure of 0.1-5 MPa; and then cooled to room temperature while maintaining the pressure to obtain the laminate with the number of layers b.

[0075] In one embodiment, the value range of a is 10-50 layers, and the value range of b is 5-20 layers.

[0076] In one of the embodiments, the mass of carbon nanotubes and carbon fibers in the PFA composite laminate accounts for 5-15% of the total composite mass.

[0077] Example 1

[0078] S1. Grind 3 parts by weight of hydrophobic carbon nanotubes CNT in perfluoropolyether and disperse by ultrasonic to obtain a CNT perfluoropolyether suspension, and polymerize with 90-99 parts of tetrafluoroethylene TFE and 1-10 parts of perfluoroalkyl vinyl ether to obtain a tetrafluoroethylene-perfluoroalkyl vinyl ether (CNT-PFA) emulsion containing CNT. Specifically, 283 g CNT was ground and ultrasonically dispersed in 300 ml perfluoropolyether; the ratio was 9200 g (about 92 mol; 97.32% by mass) tetrafluoroethylene (MW 100.01); 253 g (about 3 mol; 2.68% by mass) perfluoropropyl vinyl ether PPVE (MW266.04); 2.1 g initiator ammonium persulfate (APS; MW228.2); 20 L of deionized water (conductivity ≥18MΩ); 31 g surfactant ammonium perfluorooctanoate; 20 g ammonium carbonate (MW96) buffer material; 2 mL chain transfer agent methanol. The polymerization pressure (TFE pressure) was 2.1 MPa, the temperature was 75 ℃, PPVE was added at one time, the polymerization reaction pressure was controlled by TFE, and the CNT-PFA emulsion was obtained by in-situ reaction.

[0079] The polymerization obtained a CNT-PFA emulsion with a solid content of about 32%, which was diluted with deionized water to a solid content of about 10%, and about 50 mL of 10% hydrochloric acid was added. The mixture was stirred vigorously for 6 min, and a 20% magnesium chloride solution was added. The mixture was precipitated, washed, and centrifuged to obtain about 15,000 g of wet CNT-PFA powder.

[0080] 10000 g of wet CNT-PFA powder was dried in a rotary vacuum drying oven at 40 °C for 24 h with an absolute pressure of 0.01 MPa, and then devolatilized at 220 °C for 10 hr to obtain about 6500 g of CNT-PFA powder. The dried CNT-PFA powder was passed through a 150-mesh sieve (with a pore size of about 100 μm), and the CNT content was about 3% (mass ratio).

[0081] S2. TZ 700S (12k; tow density is about 0.83 g / m) of Weihai Guangwei Composite Materials Co., Ltd. was spread using a mechanical multi-group roller fiber expansion method to obtain a uniformly spread thin layer of tow. The original tow width was 7 mm and the thickness was 0.14 mm. After spreading, the tow width was 29.4 mm and the thickness was about 0.034 mm. The spreading ratio was about 4.2 times.

[0082] After 7 tows of yarn were spread, the 29.4 mm tows were laid flat to form a 0.2 m wide spread carbon fiber membrane layer.

[0083] The above-mentioned spread carbon fiber is immersed in a 50% (v / v) perfluoropolyether Fomblin Z Diac (molecular weight is about 2000) solution, and the solvent is trifluorotrichloroethane (F113).

[0084] CNT-PFA powder was sprayed on the surface of the impregnated spread carbon fiber in the glove box, with double-sided coating. The 0.2 m wide and 1 m long spread carbon fiber tow contained 5.81 g of carbon fiber and about 2.66 g of CNT-PFA powder (CNT content was about 80 mg), and the impregnation amount was about 31.4%.

[0085] Another portion of CNT-PFA powder was melt-extruded and granulated to obtain CNT-PFA pellets, which were then cast into films to obtain CNT-PFA cast films with a thickness of about 0.15 mm, a width of 0.4 m, a density of 2.1 g / ml, and a mass of about 315 g per square meter.

[0086] S3. A 0.2 m wide CNT-PFA cast film and a 0.2 m wide spread carbon fiber film layer are stacked in the film forming directions of 0°, 90° and 45° to form a 0.2 m×0.2 m stacked plate A, with 15 layers of cast film and 14 layers of spread carbon fiber film in the stacked plate A. The stacked plate A is placed in a high temperature resistant vacuum bag and placed in an autoclave (Shangdong Zhongke Taida Industrial Equipment Co., Ltd.), vacuum exhausted at 200-280 °C (programmed temperature rise), heated to 310-330 °C (programmed temperature rise), and molded at 4 MPa, while maintaining the pressure and program cooling at 1 °C / min, and trimmed after cooling to room temperature to obtain a laminate with a thickness of about 2.85 mm.

[0087] S4. Stack 10 layers of a 2.85 mm thick laminate at 0° and 90° in sequence, put them into a high-temperature resistant vacuum bag, put them into an autoclave, vacuum exhaust at 200-280°C, heat to 310-330°C, and compression mold them at 4 MPa. Maintain the pressure and cool by 1°C / min. After cooling to room temperature, trim the burrs to obtain a laminate with a thickness of about 29.3 mm. Trim the burrs to obtain a CNT-PFA composite laminate.

[0088] The carbon content of the above-mentioned CNT-PFA composite laminate is about 6.2%, of which CNT contributes about 43%.

[0089] Example 2

[0090] S1. Grind 3 parts by weight of hydrophobic carbon nanotubes CNT in perfluoropolyether and disperse by ultrasonic to obtain a CNT perfluoropolyether suspension, and polymerize with 90-99 parts of tetrafluoroethylene TFE and 1-10 parts of perfluoroalkyl vinyl ether to obtain a tetrafluoroethylene-perfluoroalkyl vinyl ether (CNT-PFA) emulsion containing CNT. Specifically, 283 g CNT was ground and ultrasonically dispersed in 300 ml perfluoropolyether; the ratio was 9200 g (about 92 mol; 97.32% by mass) tetrafluoroethylene (MW 100.01); 253 g (about 3 mol; 2.68% by mass) perfluoropropyl vinyl ether PPVE (MW266.04); 2.1 g initiator ammonium persulfate (APS; MW228.2); 20 L of deionized water (conductivity ≥18MΩ); 31 g surfactant ammonium perfluorooctanoate; 20 g ammonium carbonate (MW96) buffer material; 2 mL chain transfer agent methanol. The polymerization pressure (TFE pressure) was 2.1 MPa, the temperature was 75 ℃, PPVE was added at one time, the polymerization reaction pressure was controlled by TFE, and the CNT-PFA emulsion was obtained by in-situ reaction.

[0091] The polymerization obtained a CNT-PFA emulsion with a solid content of about 32%, which was diluted with deionized water to a solid content of about 10%, and about 50 mL of 10% hydrochloric acid was added. The mixture was stirred vigorously for 6 min, and a 20% magnesium chloride solution was added. The mixture was precipitated, washed, and centrifuged to obtain about 15,000 g of wet CNT-PFA powder.

[0092] 10000 g of wet CNT-PFA powder was dried in a rotary vacuum drying oven at 40 °C for 24 h with an absolute pressure of 0.01 MPa, and then devolatilized at 220 °C for 10 hr to obtain about 6500 g of CNT-PFA powder. The dried CNT-PFA powder was passed through a 150-mesh sieve (with a pore size of about 100 μm), and the CNT content was about 3% (mass ratio).

[0093] S2. TZ 700S (12k; tow density is about 0.83 g / m) of Weihai Guangwei Composite Materials Co., Ltd. was spread using a mechanical multi-group roller fiber expansion method to obtain a uniformly spread thin layer of tow. The original tow width was 7 mm and the thickness was 0.14 mm. After spreading, the tow width was 18.7 mm and the thickness was about 0.052 mm. The spreading ratio was about 2.7 times.

[0094] After 11 tows of yarn were spread, the 18.7 mm tows were laid flat to form a 0.2 m wide spread carbon fiber membrane layer.

[0095] The above-mentioned spread carbon fiber is immersed in a 50% (v / v) perfluoropolyether Fomblin Z Diac (molecular weight is about 2000) solution, and the solvent is trifluorotrichloroethane (F113).

[0096] CNT-PFA powder was sprayed on the surface of the impregnated spread carbon fiber in the glove box, with double-sided coating. The 0.2 m wide and 1 m long spread carbon fiber tow contained 9.13 g of carbon fiber and about 3.87 g of CNT-PFA powder (CNT content was about 116 mg), and the impregnation amount was about 29.8%.

[0097] Another portion of CNT-PFA powder was melt-extruded and granulated to obtain CNT-PFA pellets, which were then cast into films to obtain CNT-PFA cast films with a thickness of about 0.15 mm, a width of 0.4 m, a density of 2.1 g / ml, and a mass of about 315 g per square meter.

[0098] S3. A 0.2 m wide CNT-PFA cast film and a 0.2 m wide spread carbon fiber film layer are stacked in the film forming directions of 0°, 90° and 45° to form a 0.2 m×0.2 m stacked plate A, with 15 layers of cast film and 14 layers of spread carbon fiber film in the stacked plate A. The stacked plate A is placed in a high temperature resistant vacuum bag and placed in an autoclave (Shangdong Zhongke Taida Industrial Equipment Co., Ltd.), vacuum exhausted at 200-280 °C (programmed temperature rise), heated to 310-330 °C (programmed temperature rise), and molded at 4 MPa, while maintaining the pressure and program cooling at 1 °C / min, and trimmed after cooling to room temperature to obtain a laminate with a thickness of about 3.01 mm.

[0099] S4. Stack 10 layers of a 3.01 mm thick laminate at 0° and 90° in sequence, put them into a high-temperature resistant vacuum bag, put them into an autoclave, vacuum exhaust at 200-280°C, heat to 310-330°C, and compression mold them at 4 MPa. Maintain the pressure and cool by 1°C / min. After cooling to room temperature, trim the burrs to obtain a laminate with a thickness of about 31.2 mm. Trim the burrs to obtain a CNT-PFA composite laminate.

[0100] The carbon content of the above-mentioned CNT-PFA composite laminate is about 7.3%, of which CNT contributes about 34.4%.

[0101] Example 3

[0102] S1. Grind 3 parts by weight of hydrophobic carbon nanotubes CNT in perfluoropolyether and disperse by ultrasonic to obtain a CNT perfluoropolyether suspension, and polymerize with 90-99 parts of tetrafluoroethylene TFE and 1-10 parts of perfluoroalkyl vinyl ether to obtain a tetrafluoroethylene-perfluoroalkyl vinyl ether (CNT-PFA) emulsion containing CNT. Specifically, 283 g CNT was ground and ultrasonically dispersed in 300 ml perfluoropolyether; the ratio was 9200 g (about 92 mol; 97.32% by mass) tetrafluoroethylene (MW 100.01); 253 g (about 3 mol; 2.68% by mass) perfluoropropyl vinyl ether PPVE (MW266.04); 2.1 g initiator ammonium persulfate (APS; MW228.2); 20 L of deionized water (conductivity ≥18MΩ); 31 g surfactant ammonium perfluorooctanoate; 20 g ammonium carbonate (MW96) buffer material; 2 mL chain transfer agent methanol. The polymerization pressure (TFE pressure) was 2.1 MPa, the temperature was 75 ℃, PPVE was added at one time, the polymerization reaction pressure was controlled by TFE, and the CNT-PFA emulsion was obtained by in-situ reaction.

[0103] The polymerization obtained a CNT-PFA emulsion with a solid content of about 32%, which was diluted with deionized water to a solid content of about 10%, and about 50 mL of 10% hydrochloric acid was added. The mixture was stirred vigorously for 6 min, and a 20% magnesium chloride solution was added. The mixture was precipitated, washed, and centrifuged to obtain about 15,000 g of wet CNT-PFA powder.

[0104] 10000 g of wet CNT-PFA powder was dried in a rotary vacuum drying oven at 40 °C for 24 h with an absolute pressure of 0.01 MPa, and then devolatilized at 220 °C for 10 hr to obtain about 6500 g of CNT-PFA powder. The dried CNT-PFA powder was passed through a 150-mesh sieve (with a pore size of about 100 μm), and the CNT content was about 3% (mass ratio).

[0105] S2. TZ 700S (12k; tow density is about 0.83 g / m) of Weihai Guangwei Composite Materials Co., Ltd. was spread using a mechanical multi-group roller fiber expansion method to obtain a uniformly spread thin layer of tow. The original tow width was 7 mm and the thickness was 0.14 mm. After spreading, the tow width was 29.4 mm and the thickness was about 0.034 mm. The spreading ratio was about 4.2 times.

[0106] After 7 tows of yarn were spread, the 29.4 mm tows were laid flat to form a 0.2 m wide spread carbon fiber membrane layer.

[0107] The above-mentioned spread carbon fiber is immersed in a 50% (v / v) perfluoropolyether Fomblin Z Diac (molecular weight is about 2000) solution, and the solvent is trifluorotrichloroethane (F113).

[0108] CNT-PFA powder was sprayed on the surface of the impregnated spread carbon fiber in the glove box, with double-sided coating. The 0.2 m wide and 1 m long spread carbon fiber tow contained 5.81 g of carbon fiber and about 2.66 g of CNT-PFA powder (CNT content was about 80 mg), and the impregnation amount was about 31.4%.

[0109] Another portion of CNT-PFA powder was melt-extruded and granulated to obtain CNT-PFA pellets, which were then cast into films to obtain CNT-PFA cast films with a thickness of about 0.15 mm, a width of 0.4 m, a density of 2.1 g / ml, and a mass of about 315 g per square meter.

[0110] S3, a 0.2 m wide CNT-PFA cast film, a 0.2 m wide spread carbon fiber film layer, and another 0.2 m wide spread carbon fiber film layer are stacked in the film forming directions of 0°, 90°, and 45° to form a 0.2 m×0.2 m stacked plate A, with 15 layers of cast film and 2×14=28 layers of spread carbon fiber film in the stacked plate A. The stacked plate A is placed in a high temperature resistant vacuum bag, placed in an autoclave (Shangdong Zhongke Taida Industrial Equipment Co., Ltd.), vacuum exhausted at 200-280 °C (programmed temperature rise), heated to 310-330 °C (programmed temperature rise), and molded at 4 MPa, while maintaining the pressure and program cooling at 1 °C / min, and trimmed after cooling to room temperature to obtain a laminate with a thickness of about 3.2 mm.

[0111] S4. Stack 10 layers of a 3.2 mm thick laminate at 0° and 90° in sequence, put them into a high-temperature resistant vacuum bag, put them into an autoclave, vacuum exhaust at 200-280°C, heat to 310-330°C, and mold them at 4 MPa. Maintain the pressure and cool by 1°C / min. After cooling to room temperature, trim the burrs to obtain a laminate with a thickness of about 32.4 mm. Trim the burrs to obtain a CNT-PFA composite laminate.

[0112] The carbon content of the above-mentioned CNT-PFA composite laminate is about 8.7%, of which CNT contributes about 27.6%.

[0113] Example 4

[0114] S1. Grind 3 parts by weight of hydrophobic carbon nanotubes CNT in perfluoropolyether and disperse by ultrasonic to obtain a CNT perfluoropolyether suspension, and polymerize with 90-99 parts of tetrafluoroethylene TFE and 1-10 parts of perfluoroalkyl vinyl ether to obtain a tetrafluoroethylene-perfluoroalkyl vinyl ether (CNT-PFA) emulsion containing CNT. Specifically, 283 g CNT was ground and ultrasonically dispersed in 300 ml perfluoropolyether; the ratio was 9200 g (about 92 mol; 97.32% by mass) tetrafluoroethylene (MW 100.01); 253 g (about 3 mol; 2.68% by mass) perfluoropropyl vinyl ether PPVE (MW266.04); 2.1 g initiator ammonium persulfate (APS; MW228.2); 20 L of deionized water (conductivity ≥18MΩ); 31 g surfactant ammonium perfluorooctanoate; 20 g ammonium carbonate (MW96) buffer material; 2 mL chain transfer agent methanol. The polymerization pressure (TFE pressure) was 2.1 MPa, the temperature was 75 ℃, PPVE was added at one time, the polymerization reaction pressure was controlled by TFE, and the CNT-PFA emulsion was obtained by in-situ reaction.

[0115] The polymerization obtained a CNT-PFA emulsion with a solid content of about 32%, which was diluted with deionized water to a solid content of about 10%, and about 50 mL of 10% hydrochloric acid was added. The mixture was stirred vigorously for 6 min, and a 20% magnesium chloride solution was added. The mixture was precipitated, washed, and centrifuged to obtain about 15,000 g of wet CNT-PFA powder.

[0116] 10000 g of wet CNT-PFA powder was dried in a rotary vacuum drying oven at 40 °C for 24 h with an absolute pressure of 0.01 MPa, and then devolatilized at 220 °C for 10 hr to obtain about 6500 g of CNT-PFA powder. The dried CNT-PFA powder was passed through a 150-mesh sieve (with a pore size of about 100 μm), and the CNT content was about 3% (mass ratio).

[0117] S2. TZ 700S (12k; tow density is about 0.83 g / m) of Weihai Guangwei Composite Materials Co., Ltd. was spread using a mechanical multi-group roller fiber expansion method to obtain a uniformly spread thin layer of tow. The original tow width was 7 mm and the thickness was 0.14 mm. After spreading, the tow width was 18.7 mm and the thickness was about 0.052 mm. The spreading ratio was about 2.7 times.

[0118] After 11 tows of yarn were spread, the 18.7 mm tows were laid flat to form a 0.2 m wide spread carbon fiber membrane layer.

[0119] The above-mentioned spread carbon fiber is immersed in a 50% (v / v) perfluoropolyether Fomblin Z Diac (molecular weight is about 2000) solution, and the solvent is trifluorotrichloroethane (F113).

[0120] CNT-PFA powder was sprayed on the surface of the impregnated spread carbon fiber in the glove box, with double-sided coating. The 0.2 m wide and 1 m long spread carbon fiber tow contained 9.13 g of carbon fiber and about 3.87 g of CNT-PFA powder (CNT content was about 116 mg), and the impregnation amount was about 29.8%.

[0121] Another portion of CNT-PFA powder was melt-extruded and granulated to obtain CNT-PFA pellets, which were then cast into films to obtain CNT-PFA cast films with a thickness of about 0.15 mm, a width of 0.4 m, a density of 2.1 g / ml, and a mass of about 315 g per square meter.

[0122] S3, a 0.2 m wide CNT-PFA cast film, a 0.2 m wide spread carbon fiber film layer, and another 0.2 m wide spread carbon fiber film layer are stacked in the film forming directions of 0°, 90°, and 45° to form a 0.2 m×0.2 m stacked plate A, with 15 layers of cast film and 2×14=28 layers of spread carbon fiber film in the stacked plate A. The stacked plate A is placed in a high temperature resistant vacuum bag, placed in an autoclave (Shangdong Zhongke Taida Industrial Equipment Co., Ltd.), vacuum exhausted at 200-280 °C (programmed temperature rise), heated to 310-330 °C (programmed temperature rise), and molded at 4 MPa, while maintaining the pressure and program cooling at 1 °C / min, and trimmed after cooling to room temperature to obtain a laminate with a thickness of about 3.8 mm.

[0123] S4. Stack 10 layers of a 3.8 mm thick laminate at 0° and 90° in sequence, put them into a high-temperature resistant vacuum bag, put them into an autoclave, vacuum exhaust at 200-280°C, heat to 310-330°C, and compression mold them at 4 MPa. Maintain the pressure and cool by 1°C / min. After cooling to room temperature, trim the burrs to obtain a laminate with a thickness of about 39.1 mm. Trim the burrs to obtain a CNT-PFA composite laminate.

[0124] The carbon content of the above-mentioned CNT-PFA composite laminate is about 10.4%, of which CNT contributes about 20.7%.

[0125] Comparative Example 1

[0126] S1. Polymerize 90-99 parts of tetrafluoroethylene TFE and 1-10 parts of perfluoroalkyl vinyl ether to obtain tetrafluoroethylene-perfluoroalkyl vinyl ether (PFA) emulsion. Specifically, the ratio is 9200 g (about 92 mol; 97.32% by mass) tetrafluoroethylene (MW 100.01); 253 g (about 3 mol; 2.68% by mass) perfluoropropyl vinyl ether PPVE (MW266.04); 2.1 g initiator ammonium persulfate (APS; MW228.2); 20 L of deionized water (conductivity ≥18MΩ); 31 g of surfactant ammonium perfluorooctanoate; 20 g of ammonium carbonate (MW96) buffer substance; 2 mL of chain transfer agent methanol. The polymerization pressure (TFE pressure) is 2.1 MPa, the temperature is 75 ℃, PPVE is added at one time, and the polymerization reaction pressure is controlled by TFE to obtain PFA emulsion.

[0127] The PFA emulsion with a solid content of about 30% was obtained by polymerization, which was diluted with deionized water to a solid content of about 10%, and about 50 mL of 10% hydrochloric acid was added. The mixture was stirred vigorously for 6 min, and a 20% magnesium chloride solution was added. The mixture was precipitated, washed, and centrifuged to obtain about 14,500 g of wet PFA micropowder.

[0128] 10000 g of wet PFA powder was dried in a rotary vacuum drying oven at 40 °C for 24 h with an absolute pressure of 0.01 MPa, and then devolatilized at 220 °C for 10 hr to obtain about 6520 g of PFA powder. The dried PFA powder was passed through a 150-mesh sieve (pore size of about 100 μm).

[0129] S2. TZ 700S (12k; tow density is about 0.83 g / m) of Weihai Guangwei Composite Materials Co., Ltd. was spread using a mechanical multi-group roller fiber expansion method to obtain a uniformly spread thin layer of tow. The original tow width was 7 mm and the thickness was 0.14 mm. After spreading, the tow width was 29.4 mm and the thickness was about 0.034 mm. The spreading ratio was about 4.2 times.

[0130] After 7 tows of yarn were spread, the 29.4 mm tows were laid flat to form a 0.2 m wide spread carbon fiber membrane layer.

[0131] The spun carbon fiber was immersed in a 50% (v / v) perfluoropolyether Fomblin Z Diac (molecular weight about 2000) solution, and the solvent was trifluorotrichloroethane (F113).

[0132] PFA powder was sprayed on the surface of the impregnated spread carbon fiber in the glove box, with double-sided coating. 1 m of spread carbon fiber tow contained about 0.41 g of PFA powder.

[0133] Another part of PFA powder was melt-extruded and granulated to obtain PFA pellets, which were then cast into films to obtain PFA cast films with a thickness of about 0.15 mm, a width of 0.4 m, a density of 2.14 g / ml, and a mass of about 322 g per square meter.

[0134] S3. A 0.2 m wide PFA cast film and a 0.2 m wide spread carbon fiber film layer were directly compression molded, and the temperature was lowered by 1 °C / min while maintaining the pressure. After cooling to room temperature, the burrs were trimmed to obtain a laminate with a thickness of about 2.8 mm.

[0135] S4. Compression mold a laminate with a thickness of 2.8 mm, maintain the pressure and cool it down by 1 °C / min. After it cools to room temperature, trim the burrs to obtain a laminate with a thickness of about 28.9 mm. Trim the burrs to obtain a PFA composite laminate.

[0136] The carbon content of the above-mentioned PFA composite laminate is about 3.7%.

[0137] Table 1 Performance test results of embodiments and comparative examples (23°C, xy and z directions)

[0138]

[0139] Note:

[0140] * Some samples of the comparative example were cracked; uncracked samples were selected for testing.

[0141] ** Data in brackets are in z direction.

[0142] *** Oriented during testing, high strength along the cast stretch direction.

[0143] From the comparison in Table 1, it can be seen that since the comparative example does not use carbon nanotubes, the mechanical properties of comparative example 1 are relatively poor. The carbon fiber can be assumed to be isotropic, so the mechanical properties in the xy direction are relatively excellent. Since it is layered and stacked, the physical properties between the comparative layers are quite different, so the mechanical properties in the z direction are relatively poor.

[0144] Carbon nanotubes are close to anisotropy, and the material of the layer and the interlayer in the embodiment is consistent, so the mechanical properties in the z direction are excellent. In addition, the volume resistance of the embodiment is small.

[0145] The mechanical properties of the samples are very sensitive to the carbon fiber content. Some samples of Example 4 cracked. Adding double-layer spread carbon fiber is very sensitive to processing conditions. The bonding degree between carbon fiber and PFA is poor, indicating that the PFA layer plays a greater role in bonding.

[0146] The present application synthesizes a PFA emulsion containing carbon nanotubes CNTs by emulsion polymerization, thereby increasing the surface energy of the PFA emulsion and reducing its inertness, and then coating the CNT-PFA micropowder onto the surface of the surface-modified spread carbon fiber and drying it to obtain a spread carbon fiber prepreg; another portion of the CNT-PFA micropowder is melt-extruded, granulated and cast to obtain a PFA cast film; the dispersion of carbon nanotubes and carbon fibers in a PFA resin matrix is ​​increased, and the degree of adhesion between the carbon nanotubes and carbon fibers and the matrix resin in the PFA resin-based composite material is improved.

[0147] By in-situ synthesizing CNT-PFA, the content of CNT and carbon fiber in the composite material is increased while maintaining high temperature resistance. The tensile modulus in the z direction is increased while maintaining the tensile modulus in the xy direction. The prepared PFA composite laminate can be used in high temperature and harsh environments in semiconductor manufacturing processes.

[0148] Comparative Example 1 is not stacked in sequence at 0° and 90°, has orientation, and has high strength along the casting direction.

[0149] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed in the present application should be covered within the protection scope of the present application.

Claims

1. A method for preparing a PFA composite laminate, characterized in that: include: S1, polymerizing carbon nanotubes with tetrafluoroethylene monomers and perfluoroalkyl vinyl ether monomers to obtain a tetrafluoroethylene-perfluoroalkyl vinyl ether polymer emulsion containing carbon nanotubes, demulsifying and condensing the emulsion, washing, drying and devolatilizing the emulsion to obtain CNT-PFA micropowder; S2, coating the CNT-PFA powder onto the surface of the surface-impregnated and modified spun carbon fiber, and drying to obtain a spun carbon fiber prepreg; and melt-extruding another portion of the CNT-PFA powder to form a granulated cast film to obtain a CNT-PFA cast film; S3, alternately stacking the CNT-PFA cast film with the spun carbon fiber prepreg in different film-forming directions to form a laminated plate A, and performing vacuum exhaust molding on the laminated plate A at a certain temperature to obtain a laminated plate with a number of layers a; S4, stacking the laminated plates with a number of layers a in sequence to form a laminated plate B, and performing vacuum exhaust compression molding on the laminated plate B at a certain temperature to obtain a PFA composite laminated plate with a number of layers b.

2. The preparation method according to claim 1, characterized in that: In step S1, 1-5 parts by mass of hydrophobic carbon nanotubes are ground in a perfluoropolyether with active end groups and ultrasonically dispersed to obtain a CNT perfluoropolyether suspension, and then emulsion polymerized with 90-99 parts of tetrafluoroethylene monomer TFE and 1-10 parts of perfluoroalkyl vinyl ether monomer to obtain a tetrafluoroethylene-perfluoroalkyl vinyl ether polymer emulsion containing carbon nanotubes, and a flocculant is added for coagulation, washing, and vacuum drying and devolatilization to obtain the CNT-PFA micropowder, wherein the active end group in the perfluoropolyether with active end groups is a carboxyl group or a hydroxymethyl group.

3. The preparation method according to claim 1, characterized in that: In step S1, the perfluoroalkyl vinyl ether is at least one of perfluoromethyl vinyl ether, perfluoroethyl vinyl ether and perfluoropropyl vinyl ether.

4. The preparation method according to claim 1, characterized in that: In step S1, the vacuum drying and devolatilization temperature is 200-280°C, the pressure is 0.01-0.03 MPa, and the time is 10-24 hr.

5. The preparation method according to claim 1, characterized in that: The spread carbon fiber is obtained by processing the carbon fiber bundle by using a mechanical multi-group roller fiber expansion method.

6. The preparation method according to claim 5, characterized in that: The yarn spreading uses multiple rollers that can move up and down, and the fibers are shaken out and spread out by vibrating up and down to achieve the required width; the yarn spreading ratio is 2-5 times.

7. The preparation method according to claim 1, characterized in that: The surface of the spread carbon fiber is modified by an impregnating agent, wherein the impregnating agent is a solution of perfluoropolyether with active end groups, and the solvent in the solution of perfluoropolyether with active end groups is trifluorotrichloroethane or hexafluoroxylene.

8. The preparation method according to claim 1, characterized in that: The cast film is prepared by longitudinal casting, transverse casting or double casting, and the thickness of the CNT-PFA cast film is 0.05-0.35 mm.

9. The preparation method according to claim 1, characterized in that: The particle size of CNT-PFA powder is 1-1000 μm.

10. The preparation method according to claim 1, characterized in that: In S3, the laminated plate A is obtained by stacking the CNT-PFA cast film and the spun carbon fiber prepreg in sequence; or the laminated plate A is obtained by stacking two layers of the CNT-PFA cast film and a single layer of the spun carbon fiber prepreg in sequence, In the stacked plate A, the CNT-PFA cast films are stacked in the film forming direction at 0°, 45° or 90°.

11. The preparation method according to claim 1, characterized in that: In S3, the laminate A is heated to 260-280°C, evacuated, and then heated to 300-320°C for compression molding at a compression molding pressure of 0.1-5 MPa; and then cooled to room temperature while maintaining the pressure to obtain the laminate with a number of layers a.

12. The preparation method according to claim 1, characterized in that: In S4, the laminated plate B is heated to 260-280°C, evacuated, and then heated to 300-320°C for compression molding at a compression molding pressure of 0.1-5 MPa; and then cooled to room temperature while maintaining the pressure to obtain the PFA composite laminate with b layers.

13. The preparation method according to claim 1, characterized in that: The value range of a is 10-50 floors, and the value range of b is 5-20 floors.

14. The preparation method according to claim 1, characterized in that: The mass of carbon nanotubes and carbon fibers in the PFA composite laminate accounts for 5-15% of the total composite mass.

15. A PFA composite laminate, characterized in that: The PFA composite laminate is prepared by the method according to any one of claims 1-14.

Citation Information

Patent Citations

  • Fiber laminated composite with interlamination containing high-orientation-degree carbon nanotubes and preparation method thereof

    CN109808196A

  • Nano-material enhanced high-temperature-resistant type carbon fiber thermoplastic sizing agent and preparing method and application thereof

    CN109826013A